Motor immaturity and specific speech and language impairment: evidence for a common genetic basis - Bishop, D (Wiley-Liss, Inc., 2002)
Previous studies have found an association between motor immaturity and specific language impairment in children. Data from two twin studies were used to address the question of whether these linked deficits have a common etiology. Study 1 involved 57 MZ and 22 DZ pairs where one or both twins had specific speech/language impairment. A control group of 173 single-born children was also tested. Motor skill was assessed using a tapping task, which was carried out with left and right hands. Tapping scores were converted to scaled scores adjusted for age and sex. Unaffected twins and single-born controls did not differ in motor skill, but twins with speech and/or language impairments obtained significantly poorer tapping scores than controls. Bivariate DeFries-Fulker analysis pointed to shared genetic influence on tapping speed and a measure of speech production accuracy. In study 2, 37 twin pairs from study 1 were retested 2-3 years later and combined with 100 twin pairs from a general population sample. A timed peg-moving task was used to assess motor skill. Children with combined speech and language impairments obtained poorer peg-moving scores than unaffected children. Bivariate DeFries-Fulker analysis found significant shared genetic variance for impairments on peg-moving and on a test of nonword repetition. It is concluded that genes that put the child at risk for communicative problems also affect motor development, with the association being most evident when speech production is affected.